Effects of cationic adjuvant formulation particle type, fluidity and immunomodulators on delivery and immunogenicity of saRNA - Blakney,AK; McKay,PF; Christensen,D; Yus,BI; Aldon,Y; Follmann,F; Shattock,RJ (Journal of Controlled Release, 2019)
Self-amplifying RNA (saRNA) is well suited as a vaccine platform against chlamydia, as it is relatively affordable and scalable, has been shown to induce immunity against multivalent antigens, and can result in protein expression for up to 60days. Cationic adjuvant formulations (CAFs) have been previously investigated as an adjuvant for protein subunit vaccines; here we optimize the CAFs for delivery of saRNA in vivo and observe the immunogenicity profile in the context of both cellular and humoral immunity against the major outer membrane protein (MOMP) of Chlamydia trachomatis. We tested both liposomal and emulsion based CAFs with solid and fluid phase lipids, with or without the TLR agonists R848 and 3M-052, for in vitro transfection efficiency and cytotoxicity. We then optimized the RNA/delivery system ratio for in vivo delivery using saRNA coding for firefly luciferase (fLuc) as a reporter protein in vivo. We observed that while the fluid phase liposome formulations showed the highest in vitro transfection efficiency, the fluid and solid phase liposomes had equivalent luciferase expression in vivo. Incorporation of R848 or 3M-052 into the formulation was not observed to affect the delivery efficiency of saRNA either in vitro or in vivo. MOMP-encoding saRNA complexed with CAFs resulted in both MOMP-specific cellular and humoral immunity, and while there was a slight enhancement of IFN-γ+ T-cell responses when R848 was incorporated into the formulation, the self-adjuvanting effects of RNA appeared to dominate the immune response. These studies establish that CAFs are efficient delivery vehicles for saRNA both for in vitro transfections and in vivo immunogenicity and generate cellular and humoral responses that are proportionate to protein expression.